Successful Aging Asian Perspectives - Cheng, Sheung-Tak.; Chi, Iris.; Fung, Helene H.; Li, Lydia W.; Woo, Jean.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This book brings together state-of-the-art research on successful aging in Asian populations, and highlights how the factors that contribute to successful aging differ from those in the West. It examines the differences between the Asian and Western contexts in which the aging process unfolds, including cultural values, lifestyles, physical environments, and family structures. In addition, it examines the question of how to add quality to longer years of life. Specifically, it looks at ways to promote health, preserve cognition, maximize functioning with social support, and maintain emotional well-being despite inevitable declines and losses. Compared to other parts of the world, Asia will age more quickly as a result of the rapid socioeconomic developments leading to rising longevity, and historically low fertility rates in some countries. These demographic forces in vast populations such as China are expected to make Asia the main driver of global aging in the coming decades. As a result, researchers, professionals, policymakers, as well as the commercial sector, in both East and West, are increasingly interested in gaining a deeper understanding of aging in Asia.
Chapter 1. Successful Aging: Concepts, Reflections and its Relevance to Asia; Sheung-Tak Cheng, Helene Fung, Lydia Li, Tianyuan Li, Jean Woo, and Iris Chi -- Chapter 2. Demographic and Family Trends in Asia; Sheung-Tak Cheng -- Chapter 3. Challenges to Successful Aging in Transitional China; Lydia W. Li and Jiaan Zhang -- Chapter 4. Successful Aging and Economic Security among Older Koreans; Suk-Young Kang and JeungKun Kim -- Chapter 5. Demographic and Structural Determinants of Successful Aging in Singapore; Angelique Chan and David B. Matchar -- Chapter 6. Policy and Program Measures for Successful Aging in Japan; Vanessa Yong, Yuka Minagawa and Yasuhiko Saito -- Chapter 7. Relationships between Adults and Parents in Asia; Kyungmin Kim, Yen-Pi Cheng, Steven H. Zarit and Karen L. Fingerman -- Chapter 8. The Road to Successful Aging: Older Adults and their Families in Japan; Keiko Katagiri and Tomoko Wakui -- Chapter 9. Social Networks and the Well-Being of Older Adults in Singapore; LengLeng Tang -- Chapter 10. The Intergenerational Support and Psychological Well-Being of the Elderly in Mainland of China; Zhang Wenjuan and Du Peng -- Chapter 11. Life Satisfaction among Older Adults in Taiwan; Ju-Ping Lin -- Chapter 12. Grandparenting and Volunteering among Older Adults in Hong Kong: A Dilemma; Lou Vivian W.Q. and Tong HongMei -- Chapter 13. Implications of Temporal Trends in Chronic Illness Burden; Ruby Yu, Pui Hing Chau and Jean Woo -- Chapter 14. The Role of Nutrition in Successful Aging; Kris Yuet-Wan Lok, Ruth Suk-Mei Chan and Jean Woo -- Chapter 15. The Role of Physical Activity in Successful Aging; Jean Woo, Forest Yau and Ruby Yu -- Chapter 16. Prevention of Cognitive Decline in Later Life; Linda C.W. Lam and Wai C. Chan -- Chapter 17. In the Pursuit of Emotionally Meaningful Goals: When Would the Older Asians Display or not to Display the Positivity Effect; Xin Zhang and Yuen Wan Ho -- Chapter 18. Psychological Adaptation of Older Workers: Findings from the Western and Eastern Countries; Dannii Y. Yeung and Henry C.Y. Ho -- Chapter 19. Cross-Cultural Differences in Attitudes about Aging: Moving beyond the East-West Dichotomy; Corinna E. Löckenhoff, Diana S. Lee, Katherine M.L. Buckner, Rashidat O. Moreira, Stephanie J. Martinez and Mary Q. Sun -- Chapter 20. Successful Aging in Asia: A Concerted Effort of the State, the Family, and the Individual; Sheung-Tak Cheng, Lydia W. Li, Jean Woo, Iris Chi and Helene H. Fung.
Keywords: Social sciences; Geriatrics; Medical research; Aging; Quality of life; Social Sciences; Aging; Geriatrics/Gerontology.; Quality of Life Research; Electronic books